Prevalence and characteristics of Listeria monocytogenes in ready-to-eat chilled pot skewer products - Liu, Yuzhu; Zhang, Penghang; Wang, Di; Wang, Bowenxin; Zhang, Yi; Zhang, Xiaoyuan (Frontiers in Microbiology, 2025)
Listeria monocytogenes contamination in ready-to-eat chilled pot skewer products represent a significant public health concern in China. This study assessed the prevalence, molecular characteristics, and potential transmission risks of L. monocytogenes in 340 commercially available chilled pot skewer samples collected in 2019 and 2021. Bacterial isolation revealed an overall contamination rate of 20.6% (70/340), with no significant differences among meat-based (15.5%), vegetarian (19.5%), or mixed meat-vegetable (26.5%) products. Serogroups 1/2b, 3b, 7 (47.4%) and 1/2a, 3 (35.5%) predominated. Multilocus sequence typing (MLST) identified high-risk clones ST87 (27.6%) and ST121 (22.4%)—both associated with listeriosis outbreaks—along with rare lineages such as ST378 (1.3%). Core genome MLST (cgMLST) analysis of 76 isolates revealed extensive genetic diversity (59 cgMLST types), suggesting multiple contamination sources within production facilities. However, persistence of specific strains (≤ 2 allelic differences) across time points (2019–2021) was observed in certain manufacturers. Comparative genomics with clinical isolates from Beijing (2013–2022) revealed shared sequence types (e.g., ST87/CC87). These findings underscore the urgent need for enhanced surveillance in food processing environments. Future investigations should adopt a One Health framework to trace contamination routes and evaluate intervention control measures for this emerging food safety challenge.